A comparison between the English and Irish Poor Laws with respect to the conditions of relief - Ingram, John Kells (Statistical and Social Inquiry Society of Ireland, 1864)
I do not propose in this paper to examine the question, on which so much may be said, of the policy of a more liberal outdoor relief in the present condition of Ireland. My object is simply to state, as correctly as I can, the actual facts?the provisions respecting poor Relief now subsisting in England and Ireland?and to exhibit the differences of the powers vested in the English and Irish authorities, without discussing how far it would be expedient that any such powers should be exercised. I shall quote throughout, as far as possible, the exact words of the several documents to which I appeal, and I shall furnish such references to the sources of my information as will enable any one who wishes to verify every statement I make.
Read Wednesday, 10th February, 1864
Keywords: Poor laws; Workhouse; 314.15